Estudo da etiopatogenia da osteonecrose dos maxilares associada a medicamentos: mecanismos propostos e evidência experimental em modelos animais - Maciel, Gabriel Bassan Marinho (2025)
This Thesis is composed of two studies. The objective of the first study was to identify the factors that most influence the incidence of medication-related osteonecrosis of the jaw (MRONJ) in rodents through a systematic review and meta-analysis. A comprehensive systematic search for experimental studies of MRONJ involving rodents was conducted up to April 2025. Risk of bias was assessed using the SYRCLE tool for animal studies. The outcomes were the incidence of rats and mice that developed histological osteonecrosis and/or exposed bone or fistula in the oral cavity. A total of 119 studies were included, with 105 eligible for meta-analysis. The overall incidence of histological osteonecrosis was 28.60% (95% CI 20.24%–37.61%; I² = 90.3%) in rats and 23.81% (95% CI 8.24%–43.05%; I² = 88.6%) in mice. For exposed bone, the overall incidence was 19.96% (95% CI 13.20%–27.50%; I² = 88.9%) in rats and 8.6% (95% CI 3.2%–15.5%; I² = 75.7%) in mice. The MRONJ induction protocol and zoledronic acid (ZOL) dose were the main determinants of the histological incidence of osteonecrosis in both species, with higher incidences observed in ZOL + extraction protocols and higher ZOL doses. In rats, ZOL + extraction protocols combined with bone regularization, infection (periodontal/periapical), or dexamethasone produced the highest rates of bone exposure. In mice, ZOL combined with cyclophosphamide or dexamethasone resulted in greater bone exposure. Statistically significant publication bias was detected for bone exposure in rats, but not for other outcomes. This systematic review provided robust evidence that the induction protocol and ZOL dose are the most critical determinants of MRONJ incidence in rodents. The second study aimed to compile the main hypotheses involved in the etiopathogenesis of MRONJ. A narrative review of the literature was performed. The etiopathogenesis of MRONJ is multifactorial and not fully understood. The main hypothesis considers the disruption of bone turnover caused by antiresorptive drugs. Bisphosphonates and monoclonal antibodies inhibit osteoclast activity through different mechanisms of action, leading to the accumulation of bone microfractures. Other hypotheses also consider oral infection and inflammation, the antiangiogenic effect and toxicity of bisphosphonates on soft tissues, and the inhibition of lymphangiogenesis. As a general conclusion, knowledge of current theories for MRONJ is necessary to define future studies and protocols to minimize the incidence of this serious condition.